2011
DOI: 10.1007/s11325-010-0461-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive equations for CPAP titration in OSAS patients

Abstract: Manual or auto CPAP titration remains the best way to define the appropriate CPAP. However, predictive formulas can be useful if used with caution and always after verifying the real efficacy, particularly for patients needing higher pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
3
9
0
4
Order By: Relevance
“…Near-similar results were reported by Lacedonia et al who compared 3 predictive formulas (Stradling, Sériès, and Hoffstein), which were also used in our study, with both manual and auto-titration, and found that there were no differences in the determined pressures by Stradling and Sériès equations, and the titrated pressure, but significant difference in the pressure determined by the Miljeteig and Hoffstein equation. 25 According to Sadeghniiat-Haghighi et al, there was a statistically non-significant difference between mean pressure measured by manual method and the Loredo et al 16 formula, similar to our results; however, the differences were statistically significant when compared with calculated pressures, measured by Miljeteig and Hoffstein, 13 Lin et al, 38 and Hukins 39 equations. 37 Lee et al reported, in a study on Asians, that there was a positive correlation with no significant difference between the mean of manual titration pressure and of developed formula.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Near-similar results were reported by Lacedonia et al who compared 3 predictive formulas (Stradling, Sériès, and Hoffstein), which were also used in our study, with both manual and auto-titration, and found that there were no differences in the determined pressures by Stradling and Sériès equations, and the titrated pressure, but significant difference in the pressure determined by the Miljeteig and Hoffstein equation. 25 According to Sadeghniiat-Haghighi et al, there was a statistically non-significant difference between mean pressure measured by manual method and the Loredo et al 16 formula, similar to our results; however, the differences were statistically significant when compared with calculated pressures, measured by Miljeteig and Hoffstein, 13 Lin et al, 38 and Hukins 39 equations. 37 Lee et al reported, in a study on Asians, that there was a positive correlation with no significant difference between the mean of manual titration pressure and of developed formula.…”
Section: Discussionsupporting
confidence: 86%
“…Also, several previous studies reported no significant difference regarding therapeutic pressure value between the two techniques. [25][26][27] Other studies that depended on other titration techniques also reported near-similar results. Rosen et al 28 and Kim et al 21 carried out studies that compare PSG-guided laboratory titration and home auto-titration, and reported near-similar pressures with a statistically non-significant difference recorded for both methods.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Should they "replace" the gold standard of monitored titrations in a sleep laboratory? Although omitting the conventional procedure could potentially lead to significant financial savings and a shortening of waiting lists to perform polysomnography, manual titration of CPAP (the most labor intensive and expensive procedure) still prevails in official guidelines [26]. What is their role in "split-night" studies?…”
mentioning
confidence: 99%